Hydro-power the use of water as an alternative source of energy - Simeons, Charles (Pergamon Press, 1980)
Hydro-Power: The Use of Water as an Alternative Source of Energy deals with the use of water as an alternative source of energy. The principles of the technology involved in the extraction of energy from water for use in some other form are discussed, and some of the projects that are being undertaken in a number of countries are described. Comprised of 12 chapters, this book begins with an overview of global energy consumption and projections for energy demand, along with electricity generation using hydraulic resources and developments in the use of hydroelectric power. The next chapter focuses on the principle of wave power as an energy source, with emphasis on how power can be derived from the slow oscillation of the waves; the economics of wave power; structural design of wave energy converters; and mooring considerations. Subsequent chapters explore national wave power programs in countries such as the United Kingdom, Japan, South Africa, Egypt, Mauritius, Norway, Sweden, and the United States; tidal power and hydrogen; and energy storage and hydroelectric schemes in Europe. The final chapter assesses the environmental impact of hydroelectric power. This monograph will be a useful resource for experts and policymakers in the field of energy as well as those with little knowledge of the potential contribution that water can make to the world's energy needs.--Provided by publisher.